MODEL PENDIDIKAN BUDI PEKERTI BERBASIS CERITA ANAK UNTUK PENANAMAN NILAI ETIS-SPIRITUAL - Edy Suryanto (LITERA, 2013)
This study aims to: (1) analyze moral education needs, (2) analyze children’s stories as learning materials, and (3) design a moral education model. This was a research and development study. The subjects were Grade V students of the elementary school and the sample was randomly selected. The data sources included places and events, informants,children’s stories, and documents. The findings are as follows. It can be identified that: (a) the school has not formulated its vision and missions in the work plan; (b) the learning process in the classroom has not run well; and (c) the students’ characters are influenced by example, model, habituation, information media, environmental conditions, andregulations. Children’s stories as learning materials are arranged in the following order: (a) learning process guidelines, (b) competency attainment, (c) contents of learning materials, (d) information of values, and (e) questions to develop students’ cognitive, psychomotor,and affective aspects. The model includes: (a) inserting values into lesson plans, (b) conditioning value learning, (c) internalizing values, and (d) developing inculcated values implanted through habituation in relevant subjects.